Reduced durability of hybrid immunity to SARS-CoV-2 in immunocompromised children - Zhong, Youjia; Kottaiswamy, Amuthavalli; Ang, Chen Xiang; Li, Hui’ En; Yap, Gaik Chin; Tay, Carina J. X.; Osman, Nurul Elyana; Roslan, Siti Namirah Binte; Tan, Chee Wah; Yap, Wee Chee; Ang, Elizabeth Y.; Chan Ng, Pauline P. L.; et al. (Frontiers in Immunology, 2024)
BackgroundIn endemic COVID-19, immunocompromised children are vulnerable until vaccinated but the optimal primary vaccination regime and need for booster doses remains uncertain.MethodsWe recruited 19 immunocompromised children (post-solid organ transplantation, have autoimmune disease or were on current or recent chemotherapy for acute lymphoblastic leukemia), and followed them from the start of primary vaccination with BNT162b2 mRNA SARS-CoV-2 until 1-year post-vaccination. We investigated the quality of vaccine immunogenicity, and longevity of hybrid immunity, in comparison to healthy children.ResultsImmunocompromised children failed to produce T cell and memory B cell (MBC) responses reaching thresholds of protection after 2 doses; a third dose however improved both responses. Initially robust hybrid immunity demonstrated significantly more decline in T cell and MBC responses in immunocompromised compared to healthy children, to levels below the protective threshold by month 12.DiscussionImmunocompromised children may benefit from a 3-dose primary vaccination regime, with yearly or twice-yearly booster doses for sustained immunity.